Severe atypical juvenile pityriasis rubra pilaris diagnosed in adulthood with a dramatic improvement with ustekinumab - Rebecca L. McCarthy; Jaimie Oldham; Elsa Barbosa; Catriona Sinclair; Malvina Cunningham; Edel A. O'Toole (Wiley, 2024)
Abstract Pityriasis rubra pilaris (PRP) is a rare skin disease which manifests as a psoriasiform dermatosis and palmoplantar keratoderma and has significant clinical‐histopathological overlap with psoriasis. Recently, several case reports have demonstrated successful treatment of PRP with anti‐IL7A and anti‐IL12/anti‐IL23 monoclonal antibodies. We report a case of atypical juvenile PRP definitively diagnosed during adulthood with presence of CARD14 mutation. This case demonstrates a dramatic improvement with ustekinumab and highlights the role of genetic testing in chronic disease of diagnostic uncertainty.